Effect of grazing abandonment on arbuscular mycorrhizal diversity in Gorbeia Natural Park - Sarrionandia E.; Muguerza E.; Anza M.; Lanzén A.; Garbisu C.; Epelde L. (Mountain pastures and livestock farming facing uncertainty: environmental, technical and socio-economic challenges, 2016)
Mountain pastures in the Basque Country (northern Spain) are the result of extensive grazing dating from the Neolithic. However, current management practices are resulting in the progressive abandonment of grazing in these mountain areas. Soil microbial communities are vital for many soil processes and the delivery of essential ecosystem services; in particular, arbuscular mycorrhizal fungi play a key role in plant nutrient acquisition. The influence of grazing on the diversity of arbuscular mycorrhizal communities remains poorly explored. Then, our main objective was to evaluate the effect of the abandonment of grazing on arbuscular mycorrhizal diversity through the study of twelve grazed versus non-grazed (simulated by 100 m2 exclusions) areas in Atlantic mountain grasslands. We determined the diversity of arbuscular mycorrhizal fungi using both morphological (spore morphotyping under the microscope) and genetic (Illumina sequencing of ITS amplicons) approaches. After two years, only slight differences on arbuscular mycorrhiza were observed between grazed and non-grazed areas. In fact, the type of vegetation under which the exclusions were established accounted for the greatest amount of data variability. On the other hand, both approaches (morphological and molecular) gave similar results, highlighting the complementarity of these approaches for the study of the biodiversity of arbuscular mycorrhiza.
19. Meeting of the FAO-CIHEAM Mountain Pastures Subnetwork, 2016/06/14-16, Zaragoza (Spain)